Effect of microwave-assisted extraction on curcuminoid from turmeric and application in germinate-coated rice - Singh, Kanjana; Simapaisan, Piyawan; Utama-ang, Niramon (Food and Applied Bioscience Journal, 2017)
Curcuminoids from turmeric (Curcuma longa) provide the powerful bioactive activities, such as antiinflammatory, antibacterial, antidepressant, antitumor and gastro protective properties. The objective of this research was to investigate the effect of optimize microwave-assisted extraction (MAE) on curcuminoid from turmeric. The experiments were conducted using varying microwave power ranging from 400 to 800 watt and extraction times of 1, 2, 3, 4 and 5 minutes using 2x5 factorial experiment. The microwave power and extraction time were affected on extract yield, total phenolic content, antioxidant activity (EC50) and curcuminoids content. The extraction using the microwave power of 800 watt provided significantly higher curcuminoids, including; curcumin, demethoxycurcumin and bisdemethoxycurcumin, than that of 400 watt. The extended extraction time increased curcuminoid content then stable after 3 minutes. The optimum curcumin extraction conditions were 800 watt microwave power and 3 minutes extraction time. This condition of MAE could provide good qualities of extract; 21.00% yield, total phenolic content (161.383.56 mg GAE/g extract), EC50 (32.340.97 g/ml), curcumin (227.86±0.35 mg/g extract), demethoxycurcumin (136.26±0.56 mg/g extract) and bisdemethoxycurcumin (67.08±0.18 mg/g extract). Application of curcuminoid extract in germinate-coated rice varied curcuminoid extact at 0.5, 1.0, 1.5 and 2.0% w/v. The results showed that consumers liked coated rice with curcuminoid extract at 1.0% most. Therefore, the extraction of curcuminoid by using microwave are benefit in saving time and solvent ,and also provide high quality and efficiency of extraction.